Aplikasi Persiapan Sekolah Untuk Orang Tua Anak Down Syndrome Patient Usia 3-6 Tahun Berbasis Android - M. Agi Jabal Tariq Auzan; Nia Saurina; Firman Hadi Sukma Wijaya (Informatics Engineering Department-UWKS, 2016)
Down Syndrome is a genetic disorder that can occur in men and women, this disorder is the result of chromosomal abnormalities are not always passed down to the next descent. Chromosomal abnormalities are often found is the excess in chromosome 21, called trisomy 21. This syndrome was first described by Langdon Down in 1866, although it has long been recognized, in 1969 invented and demonstrated abnormalities on chromosome 23. Other signs such as reading book close to the eyes, mouth always so open to understand something understanding requires a long time, have sensory difficulties. In this research is expected to make an application preparatory school for paren ts of children with Down syndrome patient aged 3-6 years based on Android that aims to help children with Down syndrome can focus on getting to know the neighborhood. This study uses Waterfall covering Requirement Planning, collecting data needed sourced from literature studies Data collection of books and journals and interviews with physiotherapists in the field. This system design using UML (unified modeling language) with the creation of mobile-based applications. The trial results include reminder application that generates a specific object, such as a picture or sound is desired.